Ownership structure associated with company performance on corporate social responsibility : evidence from the Nordic stock listed companies - Larkomaa, Julia (2021)
A higher presence in topic literature and the practical field indicates the connection between the company's financial performance and subsequent corporate social responsibility performance. Supporting this, the shareholders’ demands on these matters have increased, with investors requiring more sustainability initiatives taken by the firms. This thesis focuses on different company ownership structures and their potential connection to the company performance on corporate social responsibility. More specifically, this thesis aims to study the Nordic companies’ ownership structures by focusing primarily on institutional and state owners and identify whether these owners could be associated with firm performance on different corporate sustainability metrics. The previous literature about the topic has emerged mixed results. The empirical research has focused on studying the topic by focusing on a specific industry or has been conducted on a global scale. Only a few previous studies have included Northern European companies within their samples. Therefore, a study composing a sample from Danish, Finnish, Norwegian, and Swedish publicly listed companies allow further examination, especially on this market area. The empirical part was implemented by carrying out firm and year fixed effects regression models using the sample of 286 companies listed in the Northern European (Finland, Sweden, Norway, and Denmark) stock exchanges. Both institutional and state ownership was assigned as independent variables to represent the specific ownership structure. Further on, the different variations of environmental, social and governance (ESG) scores were applied to represent the firm performance on corporate social responsibility as a dependent variable on the regression model. The findings implied no significant results between the institutional ownership and firm performance on various corporate social responsibility metrics. Companies with a higher presence of state ownership were found to perform better on corporate sustainability in general. Moreover, the higher state ownership was also identified to associate with higher performance, especially on the environmental matter. Another aim for this thesis was also to identify potential differences between the sample countries. These results implied somewhat mixed results, especially when incorporating the industry-specific characteristics into the equation.